Partitioning Carbon Dioxide Emission and Assessing Dissolved Organic Carbon Leaching of a Drained Peatland Cultivated with Pineapple at Saratok, Malaysia - Liza Nuriati Lim Kim Choo; Osumanu Haruna Ahmed (The Scientific World Journal)
Pineapples (Ananas comosus (L.) Merr.) cultivation on drained peats could affect the release of carbon dioxide (CO2) into the atmosphere and also the leaching of dissolved organic carbon (DOC). Carbon dioxide emission needs to be partitioned before deciding on whether cultivated peat is net sink or net source of carbon. Partitioning of CO2 emission into root respiration, microbial respiration, and oxidative peat decomposition was achieved using a lysimeter experiment with three treatments: peat soil cultivated with pineapple, bare peat soil, and bare peat soil fumigated with chloroform. Drainage water leached from cultivated peat and bare peat soil was also analyzed for DOC. On a yearly basis, CO2 emissions were higher under bare peat (218.8 t CO2 ha/yr) than under bare peat treated with chloroform (205 t CO2 ha/yr), and they were the lowest (179.6 t CO2 ha/yr) under cultivated peat. Decreasing CO2 emissions under pineapple were attributed to the positive effects of photosynthesis and soil autotrophic activities. An average 235.7 mg/L loss of DOC under bare peat suggests rapid decline of peat organic carbon through heterotrophic respiration and peat decomposition. Soil CO2 emission depended on moderate temperature fluctuations, but it was not affected by soil moisture.